2016
DOI: 10.1039/c6nj01303a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and NMR studies of trinuclear Mo3S4 clusters coordinated with dithiophosphate and chiral carboxylate ligands

Abstract: Introducing chirality into the Mo3S4 cluster has been achieved through coordination of (S)-mandelate and (S)-phenyllactate ligands affording new complexes as a pair of diastereoisomers, (PS) and (MS), represented in the scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[63][64] Moreover, it has been reported that the dissociation/reassociation of one of the S atom of the S,S'-donor diethyldithiophosphate ligand most likely plays a key role in the dynamic processes in solutions of Mo 3 S 4 complexes of this ligand. [47,65] A similar mechanism involving partial de-coordination of the P,P'-donor diphosphine in [Mo 3 S 4 Cl 3 (dppe) 3 ] + was proposed to explain interconversion between the P-[Mo 3 S 4 Cl 3 (dppe) 3 ] + and M-[Mo 3 S 4 Cl 3 (dppe) 3 ] + enantiomers. Such de-coordination creates a vacant position at the metal, producing a Lewis acidic site that presumably catalyzes the [(tris(tetrachlorobenzenediolato)phosphate-(V)] (TRISPHAT) anion epimerization.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[63][64] Moreover, it has been reported that the dissociation/reassociation of one of the S atom of the S,S'-donor diethyldithiophosphate ligand most likely plays a key role in the dynamic processes in solutions of Mo 3 S 4 complexes of this ligand. [47,65] A similar mechanism involving partial de-coordination of the P,P'-donor diphosphine in [Mo 3 S 4 Cl 3 (dppe) 3 ] + was proposed to explain interconversion between the P-[Mo 3 S 4 Cl 3 (dppe) 3 ] + and M-[Mo 3 S 4 Cl 3 (dppe) 3 ] + enantiomers. Such de-coordination creates a vacant position at the metal, producing a Lewis acidic site that presumably catalyzes the [(tris(tetrachlorobenzenediolato)phosphate-(V)] (TRISPHAT) anion epimerization.…”
Section: Introductionmentioning
confidence: 94%
“…[38][39][40][41][42] Our current interest in the field of catalysis is focused on trinuclear chalcogenide molybdenum and tungsten clusters. [43][44][45] Within the last decade, the groups in Novosibirsk and Castellon have developed synthetic approaches for the functionalization of trinuclear M 3 S 4 (M = Mo, W) clusters with homobidentate chelating ligands such as S,S'-donor dithiophosphates, [46][47][48] P,P'-donor diphosphines, [49][50][51][52] N,N'-donor diamines [53][54][55] or diimines [54,[56][57][58][59] . The Mo 3 S 4 complexes, functionalized in this way, are excellent chemoselective catalysts for reduction of nitroarenes with different reducing agents.…”
Section: Introductionmentioning
confidence: 99%